1977
DOI: 10.1093/nar/4.5.1539
|View full text |Cite
|
Sign up to set email alerts
|

Rates of formation and thermal stabilities of RNA:DNA and DNA:DNA duplexes at high concentrations of formamide

Abstract: The thermal stabilities of RNA:DNA hybrids are substantially greater than those of DNA:DNA duplexes in aqueous electrolyte solutions containing high concentrations of formamide. Association rates to form DNA:DNA duplexes and DNA:RNA hybrids have been measured in these solvents. There is a temperature range in which DNA:DNA rates are negligible and RNA:DNA rates close to optimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
238
0
2

Year Published

1978
1978
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 708 publications
(245 citation statements)
references
References 23 publications
5
238
0
2
Order By: Relevance
“…In 4 M NaC104 at 700C (the Topt for RNA:DNA association in this system) the observed is 8. It has been reported that the DNA:DNA reassociation rate constant in 80% formamide, 0.4 M NaCl is about 1/3 to 1/3.6 of that in aqueous solution (8 There is a very clear decrease in the apparent limiting value of the degree of reaction in 4 M NaC104 as the temperature decreases from 70C to 40C. We believe that several factors may contribute to this phenomena.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In 4 M NaC104 at 700C (the Topt for RNA:DNA association in this system) the observed is 8. It has been reported that the DNA:DNA reassociation rate constant in 80% formamide, 0.4 M NaCl is about 1/3 to 1/3.6 of that in aqueous solution (8 There is a very clear decrease in the apparent limiting value of the degree of reaction in 4 M NaC104 as the temperature decreases from 70C to 40C. We believe that several factors may contribute to this phenomena.…”
Section: Discussionmentioning
confidence: 63%
“…The difference in stability between RNA:DNA hybrids and DNA:DNA duplexes in the usual aqueous solutions of non-denaturing salts (8,19,16) is much smaller than the differences observed for the above mentioned electrolytes and for formamide (8).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In practical terms, this result indicates that the elution conditions required to recover acceptable yields of messenger-sized cRNA from DNA-Sephadex are 90% formamide, 0.2 M NaCl and 70°C, but the data also clearly show that ethanolamine-blocked CNBr-activated Sephadex is a reactive matrix, and therefore not ideal for nucleicacid-affinity chromatography. An improvement to the method described here is suggested by the work of Casey and Davidson [35] who have reported on the thermal stabilities of DNA . RNA duplexes in aqueous electrolyte solutions containing high concentrations of formamide.…”
Section: Resultsmentioning
confidence: 99%
“…These DNA fragments (approx. 1 x 10m3 pg of coding sequence) were hybridized to adult polyribosomal poly(A) + RNA (30 pg) under conditions that allow RNA-DNA hybridization, but do not allow DNA-DNA reannealing (Casey and Davidson, 1977;Levy et al, 1982). The R,,t value achieved was 460, which is approx.…”
Section: (C) Determination Of Transcription Orientationmentioning
confidence: 99%